Match Card Game For Education About Traditional Kingdom in Indonesia: Match Card Game untuk edukasi mengenai kerajaan Tradisional di Indonesia - Abdillah, David Fahmi; K, Ilham Basri; lambang , Yanuangga Galahart; Khotiah, Titiek; Dijaya, Rohman (Procedia of Engineering and Life Science, 2023)
Indonesia is one of the country that has an old history that can be tracked until 1000 years, even before Indonesia got invaded by Netherlands. Many kingdoms that rise and fall or replaced by another kingdom, and many rulers that have bloodline with another rulers in different kingdom. Each kingdom has different culture background that based on different religion, where we can see about their culture development from kingdoms from the past. Game education is one of the tools for learning that can be used for modern entertainment game that give education point or knowledge so the player can learn while playing the game. Match card game is a game where player match the image with the same image and finish it by matching all the cards with the same image. In this game, by borrowing match game mechanic, we modified it with player need to choose a Question Card and match it with the correct Answer Card. There is 3 stages in the game that separate it with Hindu’s kingdoms, buddha kingdoms and Muslim kingdoms in Indonesia. Player then will got a questioner about the topic in the game. The result we got that the players has improvement about the old kingdoms in Indonesia. And we got positive reaction about the game and they interested to play it again and gain a higher score than before.